2005
DOI: 10.1182/blood-2004-07-2716
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical profiling of caspase signaling pathways predicts clinical response to chemotherapy in primary nodal diffuse large B-cell lymphomas

Abstract: We used biopsy specimens of primary nodal diffuse large B-cell lymphoma (DLBCL) to investigate whether the inhibition of caspase 8 and/or 9 apoptosis signaling pathways predicts clinical outcome. Expression levels of cellular FLICE inhibitory protein (c-Flip) and numbers of active caspase 3-positive lymphoma cells were used to determine the status of the caspase 8-mediated pathway. Expression levels of Bcl-2 and X-linked inhibitor of apoptosis (XIAP) were used to determine the status of the caspase 9-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 50 publications
7
79
1
Order By: Relevance
“…Nevertheless, more likely explanation is that caspase-3 cannot be evaluated properly because all tumor cells, as well as non-tumor cells, express this form of caspase-3. To avoid this problem, more recent studies tested the expression of the active form of caspase-3 [16,17]. However, it was demonstrated that prognostic value of active caspase-3 is closely related to expression levels of other apoptosis-related proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, more likely explanation is that caspase-3 cannot be evaluated properly because all tumor cells, as well as non-tumor cells, express this form of caspase-3. To avoid this problem, more recent studies tested the expression of the active form of caspase-3 [16,17]. However, it was demonstrated that prognostic value of active caspase-3 is closely related to expression levels of other apoptosis-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that immunohistochemical localization of caspase-3 can be correlated with clinical outcome in DLBCL [15]. More recent studies evaluated expression of active (cleaved) caspase-3 [16,17]. However, the expression of active caspase-3 is generally very low and it may be difficult to determine if active caspase-3 positive cells are indeed neoplastic.…”
mentioning
confidence: 99%
“…23,24 The BCL2-IGH translocation is present in LY10 cells (CY and YLW, data not shown). Downregulation of BCL2 may, therefore, account for the cell death induced by dasatinib in LY10 cells.…”
Section: Effects Of Dasatinib On Cell Cycle Regulatory Proteins and Amentioning
confidence: 99%
“…Very few reports on a prognostic influence of CASP9 expression in cancer have been published until now, with conflicting results. In large B-cell lymphomas, inhibition of CASP9 was strongly associated with a poor response to chemotherapy (19). However, as described here, other studies have Results are presented in log10 scale and are expressed as fold-change.…”
Section: Discussionmentioning
confidence: 97%